2009
DOI: 10.1080/15367100903200429
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Self-Determination and Self-Directed Employment Planning for Young Women With Disabilities

Abstract: Self-determination, choice, and preference have become important issues in vocational rehabilitation and have long been staples of social work practice. This article provides an overview of a model, the self-determined career development model, which is designed to enable people with disabilities to self-direct planning that leads to employment. Specifically, this model is applied to young women with intellectual and developmental disabilities to obtain nontraditional employment through self-regulated, customi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…With regard to the SDCDM, worked with vocational rehabilitation counselors to implement the SDCDM, and found that adults with disabilities who were supported to use the model made progress on self-selected employment goals, and felt that they had gained important skills. Wehmeyer et al (2009) also used the SDCDM as part of a larger intervention package with young women with developmental disabilities, suggesting that they found the model useful and effective in setting and pursing career development goals. Shogren et al (2016) examined implementation of the SDCDM with direct support providers as facilitators, examining the impacts on self-determination of adults with intellectual and developmental disabilities served by support provider organizations in the community, finding that the SDCDM influenced self-determination outcomes.…”
Section: Interventions To Promote Self-determination and Post-school mentioning
confidence: 99%
“…With regard to the SDCDM, worked with vocational rehabilitation counselors to implement the SDCDM, and found that adults with disabilities who were supported to use the model made progress on self-selected employment goals, and felt that they had gained important skills. Wehmeyer et al (2009) also used the SDCDM as part of a larger intervention package with young women with developmental disabilities, suggesting that they found the model useful and effective in setting and pursing career development goals. Shogren et al (2016) examined implementation of the SDCDM with direct support providers as facilitators, examining the impacts on self-determination of adults with intellectual and developmental disabilities served by support provider organizations in the community, finding that the SDCDM influenced self-determination outcomes.…”
Section: Interventions To Promote Self-determination and Post-school mentioning
confidence: 99%
“…Scholars agree that entrepreneurship approach is an alternative empowerment approach that support PWD to have better live [6,[8][9][10]. Kitiching argues entrepreneurship approach possible to increase PWD's labor market participation specifically, and social inclusion more generally through entrepreneurship program [6].…”
Section: B Entrepreneurship Approach On Pwd Empowermentmentioning
confidence: 99%
“…Although there are robust arguments about relevance of entrepreneurship approach on PWD, conditional factors about the success approach should be take into account. Wehmeyer et al founds that self-determination, to both the right and capacity of people to exert control over and direct their lives, and existence of social workers, have significant role in vocational rehabilitation or entrepreneurship for PWD [9]. In more detail, Yamamoto and Alverson, found that contributing factors of this program are accountability systems, level of supports, and individual characteristics [10].…”
Section: B Entrepreneurship Approach On Pwd Empowermentmentioning
confidence: 99%
“…The self-determination career development model (SDCDM) was developed to teach individuals with disabilities self-determination skills, and to apply these skills to identifying and pursuing career goals (Wehmeyer et al, 2009). The SDCDM is based on Wehmeyer's (1999) conceptual framework of self-determination.…”
Section: Introductionmentioning
confidence: 99%
“…The SDCDM is based on Wehmeyer's (1999) conceptual framework of self-determination. Using nonexperimental research designs to evaluate the SDCDM, participants made gains on the number of job-related goals, which they set and attained (Benitez, Lattimore, & Wehmeyer, 2005;Wehmeyer, 2010;Wehmeyer et al, 2003;Wehmeyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%